The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1080/00288330.1989.9516342
|View full text |Cite
|
Sign up to set email alerts
|

Picophytoplankton in the Hauraki Gulf, New Zealand

Abstract: Qualitative and quantitative data for picophytoplankton from the Hauraki Gulf, northeast New Zealand, were gathered from May 1986 to February 1987. Records for both whole and sizefractionated samples (net-, nano-, and picophytoplankton) allowed the relative contribution by the picophytoplankton to total biomass and overall rates of carbon fixation to be estimated. Picophytoplankton represented a mean value of over 30% of the total chlorophyll a in winter and c. 20% in other seasons. In terms of total carbon fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The volume of the reniform-shaped cells was larger than that of the coccoid cells. This feature was also noted in both oceanic and coastal waters (Booth and Sondergaard, 1989;Glover et al, 1986). Larger volume of reniform-shaped cells might be the results of greater pigment contents and the cells might change to this shape under low light conditions to strengthen its photosynthetic efficiency.…”
Section: Spatial Distribution Of Picophytoplankton and Nanophytoplankmentioning
confidence: 85%
“…The volume of the reniform-shaped cells was larger than that of the coccoid cells. This feature was also noted in both oceanic and coastal waters (Booth and Sondergaard, 1989;Glover et al, 1986). Larger volume of reniform-shaped cells might be the results of greater pigment contents and the cells might change to this shape under low light conditions to strengthen its photosynthetic efficiency.…”
Section: Spatial Distribution Of Picophytoplankton and Nanophytoplankmentioning
confidence: 85%
“…Continuous feeding is possible due to the year round availability of fish (Kendrick and Francis 2002) and zooplankton (Jillett 1971) within these productive waters. The East Auckland Current is the primary reason for this high productivity (Booth and Sondergaard 1989, Chang et al . 2003), and explains the extensive marine biodiversity within this region (Kendrick and Francis 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Continuous feeding is possible due to the year round availability of fish (Kendrick and Francis 2002) and zooplankton (Jillett 1971) within these productive waters. The East Auckland Current is the primary reason for this high productivity (Booth andSondergaard 1989, Chang et al 2003), and explains the extensive marine biodiversity within this region (Kendrick and Francis 2002). Previously, authors E263 have suggested that Bryde's whale abundance is strongly related to upwelling systems which result in higher rates of primary productivity, as demonstrated off Chile (Gallardo et al 1983), eastern tropical Pacific (Ballance et al 2006) and for the inshore form off South Africa (Best 1960).…”
Section: Seasonal Occurrence and Geographic Distributionmentioning
confidence: 98%
“…Strong coastal upwellings make the study area an extremely productive (Booth & Søndergaard 1989) and biologically diverse region (Stockin et al 2008b). Seasonal upwelling occurs in the later austral winter to early spring, when prevailing westerly winds introduce nutrients into surface waters, which elevates spring chlorophyll-a levels in the outer Gulf and along the outer shelf (Chang et al 2003;Zeldis et al 2004).…”
Section: Study Areamentioning
confidence: 99%